2017
DOI: 10.12799/jkachn.2017.28.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Causal Relationship between Social Activities and Health with Reference to the Cognitive Function Level among Community-dwelling Older Adults: A Cross-Lagged Panel Analysis

Abstract: Purpose: The aim of this study is to examine the reciprocal causal relationship between social activities and health with reference to the cognitive function level among community-dwelling older adults. Methods: We conducted a longitudinal data analysis using the 4 th (Time 1) and 5 th (Time 2) waves from the Korean Longitudinal Study of Ageing adopting cross-lagged panel analysis (CLPA). Results: A total of 3,473 community-dwelling older adults were included in the analysis: 2,053 in the normal cognitive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…Thirdly, the study's examination of the longitudinal relationship between depression and cognitive function revealed that higher initial depression levels were associated with lower initial cognitive function levels and a more rapid decline in cognitive function over time. These findings are consistent with previous research indicating that depression is a significant factor influencing cognitive impairment and dementia [15][16][17][18][19][20]. These findings are also applicable to older individuals living alone in South Korea.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thirdly, the study's examination of the longitudinal relationship between depression and cognitive function revealed that higher initial depression levels were associated with lower initial cognitive function levels and a more rapid decline in cognitive function over time. These findings are consistent with previous research indicating that depression is a significant factor influencing cognitive impairment and dementia [15][16][17][18][19][20]. These findings are also applicable to older individuals living alone in South Korea.…”
Section: Discussionsupporting
confidence: 92%
“…Acknowledging these global shifts, several studies have identified depression as a significant contributing factor to cognitive impairment, including dementia [15][16][17][18][19][20]. A decline in economic capabilities and social relationships is common among older adults due to physical aging, illnesses, and stressors such as the loss of a spouse or friends.…”
Section: Introductionmentioning
confidence: 99%
“…라는 인지적으로 취약한 독거노인을 치매 위험이 높은 집단으로 분 류하고, 전국 치매안심센터를 통해 인지 선별검사를 포함한 치매 예 방 교육 및 상담 등의 집중 관리 서비스를 제공하고 있다 [7]. 하지만 국가의 제도적 대응 외에도 독거노인의 인지 기능 저하와 관련 있는 연령 [5,6], 교육수준 [8,9], 운동 [6], 거주 지역 [5], 우울 [6,[9][10][11], 성별 [9], 도구적 일상생활능력 [6], 흡연, 음주 등 생활습관 [6,9], 건강 상 태 [11] 등에 대한 체계적 관리 방안이 필요하다. 즉, 치매의 발병 위 험을 낮추기 위한 개인적인 관심과 노력이 요구된다.…”
unclassified
“…하지만 독거노인을 대상으로 실시한 국내 인지 기능 관련 연구는 거주 지역에 주목하기보다 가구형태와의 상호관련성을 확인 [6], 가 구형태별 인지 기능 저하 위험요인 비교 [5], 치매 위험요인을 중심으 로 인지 기능 저하 영향요인을 확인 [8]하거나 상호인과관계 확인 [10], 독거노인의 성별에 주목한 종단 분석 [16] 등 개인의 특성과 관 련된 연구가 수행되었다. 현재 거주 지역 관련 연구는 거의 없는 실 정이며, 농촌과 도시 노인의 인지 기능을 비교한 연구 [12]…”
unclassified
“…In prevention research, many studies have been concerned with the bidirectional, dynamic interplay of psychological, medical, and health-related variables and constructs. For instance, physical activity (PA) was related to academic performance (Aaltonen et al, 2016), executive functioning (Farina, Tabet, & Rusted, 2016), depression (Lindwall, Larsman, & Hagger, 2011; Stavrakakis, de Jonge, Ormel, & Oldehinkel, 2012), fear-avoidance beliefs (Leonhardt et al, 2009), allostatic load (Read & Grundy, 2014), and habit (van Bree et al, 2017); health was related to social activities (Kim & Yoon, 2017) and depression (Kim, Noh, Park, & Kwon, 2014). The argumentation in such studies often starts with the observation that two variables are associated, but that the directionality of the association is unclear.…”
mentioning
confidence: 99%